Socialization and Education on Electrical Occupational Safety for Community Members and the People’s Labor Union in Yogyakarta - Hendrawati, Lulus Suci; Rudyarti, Edwina; Suryana, Anna; Lelitasari; Purba, Yunita Sari; Uci Sulandari; Defi Arjuni (Society : Jurnal Pengabdian Masyarakat, 2026)
The high rate of occupational accidents caused by electrical hazards, particularly in the informal sector, indicates the need to improve occupational safety education. This community service activity aims to enhance the knowledge and skills of community members and workers affiliated with the People’s Labor Union (SERBUK) Yogyakarta regarding electrical hazards, the use of personal protective equipment (PPE), and emergency response procedures. The implementation methods included educational sessions, interactive discussions, and fire evacuation simulations. The activity was conducted on August 28, 2025, and attended by 30 participants. The evaluation results showed a significant improvement in participants’ understanding of electrical occupational health and safety. This activity successfully fostered collective awareness of the importance of a safety culture and the sustainability of occupational safety education.